Analysis Of Application - Based Bill Transaction Information System To Increase Customer Payment Awareness (Case Study Of PDAM Tirtauli Pematangsiantar City) - Marintan Saragih; Vitryani Tarigan (Jurnal Ilmiah Accusi, 2026)
This study aims to analyze the accounting information system of cash receipts and expenditures at PDAM Tirtauli Pematangsiantar and assess the effectiveness of its implementation. Accounting information systems have an important role in managing financial data into accurate and usable information in decision-making. The research method used is a descriptive method with a qualitative approach. Data collection techniques are carried out through interviews, observations, and documentation. The results of the study show that the accounting information system for cash receipts and cash expenditures at PDAM Tirtauli has clear procedures and runs according to the provisions. However, in its implementation, there are still several weaknesses such as suboptimal separation of duties, lack of supervision, and documentation that is not well organized. This shows that internal control has not been running optimally. Therefore, improvements are needed in the system in order to increase the effectiveness and efficiency of cash management